ANALYSIS OF THE INFLUENCE OF THE VARIATION OF THE FUNCTIONAL GEOMETRY OF THE CUTTING TOOL ON THE CUTTING FORCE DURING TURNING WITH TRANSVERSE FEED - Mădălin TOMESCU; Cosmin IONESCU (Fiabilitate şi Durabilitate, 2024)
The good development of the chipping processing processes is greatly influenced by the rigidity of the technological system, but also by the size and variation of the forces that appear during the chipping processing process. The force required to detach the chip must be known both for the design of the machine tool, the devices and the cutting tools, and for establishing some limit values of its size, depending on the strength or, in most cases, the rigidity of the processed semi-finished product. The paper presents the variation of the values of the cutting force for the transverse turning operation due to the variation of the functional geometry of the cutting tool during the cutting process in order to optimize the geometry of the active part of the cutting tool. Thus, in the work, the recommended optimal constructive geometry of a lathe knife that can be used for turning a part with the diameter 150mm , as well as the parameters of the cutting regime, was established. Under these conditions, a correlation was identified between the values of the functional geometric parameters of the cutting tool used for transverse turning of C45 steel (1.0503): EN 10277-2-2008-  150mm and the cutting forces that occur during cutting